Daya Saing Komoditas Kentang di Kabupaten Banjarnegara, Jawa Tengah Pendekatan Policy Analysis Matrix (PAM) (The Competitiveness of Potato Commodities in Banjarnegara-Central Java, using Policy Analysis Matrix (PAM)) - Doni Sahat Tua Manalu; Suharno Suharno; Netti Tinaprilla (IPB University, 2014)
Agricultural policy in any country causes intended and unintended impact on related sectors. Essentially, introduction of new commodity policy changes incentive structure to participating farmers of the sector. Policy analysis matrix (PAM) provides a framework and tools of analysis regarding the impact of policy change in simple but quantitative measure. This PAM analysis concerned mainly on the potato sector at sample area, Banjarnegara. The aim of this study was to analyze the impact of policies on the competitiveness of potatoes in Banjarnegara district, Central Java. Location of the research conducted in Banjarnegara district, the analysis method that used in this study are qualitative and quantitative analysis. Qualitative method is used to study the location decribe general description while quantitative method is used to analyze the competitiveness of the potato and the impact of government policies that analyzes the Policy Analysis Matrix. The analysis showed that potato farming in Central Java Banjarnegara district competitiveness, however, a policy that protects the price of potato output needs to be done so that the domestic potato can compete with the price of imported potatoes.Keywords : Competitiveness, Potatoes, Policy Analysis Matrix (PAM)